2017
DOI: 10.1186/s12935-017-0495-6
|View full text |Cite
|
Sign up to set email alerts
|

Matrine combined with cisplatin synergistically inhibited urothelial bladder cancer cells via down-regulating VEGF/PI3K/Akt signaling pathway

Abstract: BackgroundCisplatin is one of the first-line drugs for urothelial bladder cancer (UBC) treatment. However, its considerable side effects and the emergence of drug resistance are becoming major limitations for its application. This study aimed to investigate whether matrine and cisplatin could present a synergistic anti-tumor effect on UBC cells.MethodsCell viability assay was used to assess the suppressive effect of matrine and cisplatin on the proliferation of the UBC cells. Wound healing assay and transwell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 35 publications
0
38
1
Order By: Relevance
“…Our previous studies have also provided evidence of some natural agents with potential antitumour activity in combination with other therapeutic drug, such as Tan IIA (Xie et al, ) and matrine (Liao et al, ). However, there is no evidence at the cellular level or from animal models demonstrating such an effect of the combination of Tan IIA with DDP on NSCLC progression.…”
Section: Discussionmentioning
confidence: 87%
“…Our previous studies have also provided evidence of some natural agents with potential antitumour activity in combination with other therapeutic drug, such as Tan IIA (Xie et al, ) and matrine (Liao et al, ). However, there is no evidence at the cellular level or from animal models demonstrating such an effect of the combination of Tan IIA with DDP on NSCLC progression.…”
Section: Discussionmentioning
confidence: 87%
“…In addition, the decrease in the proportion of S phase cells suggested that cell proliferation was inhibited by the treatments. The data also showed that the berberineñmatrine combination had a more significant effect than either drug alone (34)(35).…”
Section: Compound-induced Cell Cycle Arrest In Cervical Cancer Cellsmentioning
confidence: 89%
“…The streptomycin/penicillin of 100 units/mL (Invitrogen, Carlsbad, CA, USA) and 10% fetal bovine serum (FBS, Gibco) were also added in. MAT (Figure 1, Sigma, St. Louis, MO, US) was diluted with ddH 2 O to IC50 24 and was utilized for cells for 24 h through a filter.…”
Section: Cell Culture and Treatmentmentioning
confidence: 99%